Challenges of model-based definition for high-value manufacturing - Goher, Kamran; Shehab, Essam; Al-Ashaab, Ahmed (IOS, 2019)
Manufacturing Industry is moving towards adoption of 3D models as the ultimate authoritative source for complete product definition replacing 2D drawings, which is called “Model-Based Definition”. Starting its journey from geometric information on design, manufacturing, and inspection, the targets are to achieve the ultimate goal of lifecycle model based enterprise, requiring MBD to be more comprehensive and challenging structure of information instead of just a geometric model. The industry has not yet fully achieved implementation of MBD to whole product lifecycle. This journey is long and tough, and we are still at an early stage, but it will be a decisive factor in gaining competitive advantage by the early adopters, especially in high-value manufacturing. Complete adoption of MBD has several issues and challenges that need to be addressed. This paper presents a review of current literature, intending to cover present state of knowledge, issues, challenges, and future research directions, in the development and adoption of MBD.
Keywords: Model-Based Definition; Model-Based Enterprise; Challenges